The Effect of Pregnant Woman Classes on Stunting Prevention Efforts - Utami, Risqi; Hassan, Hafizah Che; Umar, Nur Syazana (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
One of the nutritional issues that continues to be a problem in Indonesia is stunting. For the time being, the percentage of babies and toddlers who are stunted is still relatively high, which means that it is necessary to lower it. The reduction in the number of kids who are stunted can be prevented as early as feasible. Classes for pregnant women are one method of preventing stunting. These classes are designed to educate and enlighten pregnant women about stunting, which is one of the ways that stunting can be prevented. This study was conducted to determine the impact that classes for pregnant women have on the prevention of stunting issues. This secondary research utilized a literature review approach by examining pertinent information on a specific topic. Articles were sourced from the Pubmed and Google Scholar databases using the